More Notes on the “Print Islam” in Early 20th Century Malay-Indonesian World: Cairene Reformism and Its Traditionalist Counterpart - Safari; Muhammad Afif Amrulloh; Asep Musadad (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: The article examines aspects of three Islamic-oriented periodicals published in the early twentieth century: al-Imām (1906-1908), al-Munīr (1911-1915), and al-Mīzān (1918-1922). Within what Kersten refers to as the “Print Islam,” existing scholarship has largely concentrated on reformist publications – particularly al-Imām and al-Munīr – while their traditionalist counterparts remain comparatively under-studied. Addressing this gap, the article highlights the traditionalist response by conducting a preliminary study of al-Mīzān, an important periodical associated with traditionalist circles. As the principal vehicles for transmitting Cairene reformism in the Malay-Indonesian world, the periodicals al-Imām and al-Munīr, published by kaum muda (youth-led reformist camp), vigorously criticized established religious practices while also initiating discussions on nationhood within the reformist Islamic movement. In response to reformist challenges, the kaum tua launched al-Mīzān to defend inherited religious practices while engaging contemporary issues through a traditionalist lens grounded primarily in Syāfiī fiqh. During the phase of “Print Islam”, both reformist and traditionalist actors contributed to shaping the trajectory of Islamic history in the archipelago, not only through contestations over religious discourse but also by establishing precedents for further imagined nationhood in religious terms. Abstrak: Artikel ini bertujuan untuk mengkaji beberapa aspek dalam tiga majalah berorientasi Islam yang diterbitkan pada awal abad ke-20: al-Imām (1906-1908), al-Munīr (1911-1915), dan al-Mīzān (1918-1922). Dalam apa yang disebut Kersten sebagai print Islam (Islam [dalam media] Cetak), kajian yang ada sebagian besar terkonsentrasi pada publikasi reformis – khususnya al-Imām dan al-Munīr – sementara rekan-rekan tradisionalisnya relatif jarang dikaji. Berawal dari kesenjangan tersebut, artikel ini menyoroti respons tradisionalis dengan melakukan kajian awal terhadap al-Mīzān, sebuah majalah penting yang terkait dengan kalangan tradisionalis. Sebagai wahana utama penyebaran reformisme Kairo di dunia Melayu-Indonesia, majalah al-Imām dan al-Munīr yang diterbitkan oleh kaum muda (kelompok reformis) secara gencar mengkritik praktik-praktik keagamaan yang mapan sekaligus memulai diskusi tentang kebangsaan dalam bingkai Islam reformis. Sebagai respons terhadap tantangan reformis, kaum tua (kelompok tradisionalis) meluncurkan berkala al-Mīzān untuk membela praktik-praktik keagamaan yang diwariskan turun-temurun, sekaligus membahas isu-isu kontemporer melalui lensa tradisionalis yang utamanya berlandaskan fikih Syāfi’ī. Selama fase print Islam, baik aktor reformis maupun tradisionalis berkontribusi dalam membentuk lintasan sejarah Islam di kepulauan ini, tidak hanya melalui kontestasi atas wacana keagamaan, tetapi juga dengan menciptakan preseden untuk pembicaraan tentang kebangsaan yang dibayangkan lebih lanjut dalam aksen keagamaan.